2016
DOI: 10.1371/journal.pone.0167335
|View full text |Cite
|
Sign up to set email alerts
|

Oldenlandia diffusa Extract Inhibits Biofilm Formation by Haemophilus influenzae Clinical Isolates

Abstract: Oldenlandia diffusa has been empirically used as a therapeutic adjunct for the treatment of respiratory infections. To establish the basic evidence of its clinical usefulness, antimicrobial and biofilm inhibitory activities of an O. diffusa extract were examined against clinical isolates of Haemophilus influenzae, a major causative pathogen of respiratory and sensory organ infections. No significant growth inhibitory activity was observed during incubation for more than 6 h after the extract addition into a cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Natural and synthetic compounds have also been investigated for the control of biofilms formed by H. influenzae. For instance, pyrazol derivatives (Kosikowska et al 2014), chalcones (Kunthalert et al 2014), plant extracts (Wajima et al 2016), nitric oxide (Collins et al 2016), proteins (Dawe et al 2017), and honey (Newby et al 2018), among others, have shown positive effects.…”
Section: Novel Strategies Targeting Otitis Media Biofilmsmentioning
confidence: 99%
“…Natural and synthetic compounds have also been investigated for the control of biofilms formed by H. influenzae. For instance, pyrazol derivatives (Kosikowska et al 2014), chalcones (Kunthalert et al 2014), plant extracts (Wajima et al 2016), nitric oxide (Collins et al 2016), proteins (Dawe et al 2017), and honey (Newby et al 2018), among others, have shown positive effects.…”
Section: Novel Strategies Targeting Otitis Media Biofilmsmentioning
confidence: 99%
“…11 To discover agents exhibiting antivirulence activity other than antimicrobial agents, we have screened various herbal medicines, including the Kampo medicines. [12][13][14][15] Although some Kampo medicines were used successfully to treat pyogenic dermatitis, 16 no case was reported of patients with impetigo being treated by any Kampo medicines. Decreased production and virulence of ET lead to the alleviation of the symptoms of impetigo and prevent SSSS.…”
Section: Introductionmentioning
confidence: 99%
“…However, a heavy use of antibiotics causes an increase in bacterial resistance, limiting the continued use of antimicrobial treatment for acne . Some natural medicines with antimicrobial and antipathogenic activity have been reported . Kampo medicines, traditional Japanese herbal medicines, have been used for acne treatment.…”
Section: Introductionmentioning
confidence: 99%
“…6 Some natural medicines with antimicrobial and antipathogenic activity have been reported. 7,8 Kampo medicines, traditional Japanese herbal medicines, have been used for acne treatment. Of these, Keigairengyoto, Seijoboufuto and Jumihaidokuto are considered as one of the options in acne treatment guidelines.…”
Section: Introductionmentioning
confidence: 99%